3D Bioprinting for Cartilage and Osteochondral Tissue Engineering. Issue 22 (14th August 2017) - Daly, Andrew C.; Freeman, Fiona E.; Gonzalez‐Fernandez, Tomas; Critchley, Susan E.; Nulty, Jessica; Kelly, Daniel J.
Abstract: Significant progress has been made in the field of cartilage and bone tissue engineering over the last two decades. As a result, there is real promise that strategies to regenerate rather than replace damaged or diseased bones and joints will one day reach the clinic however, a number of major challenges must still be addressed before this becomes a reality. These include vascularization in the context of large bone defect repair, engineering complex gradients for bone‐soft tissue interface regeneration and recapitulating the stratified zonal architecture present in many adult tissues such as articular cartilage. Tissue engineered constructs typically lack such spatial complexity in cell types and tissue organization, which may explain their relatively limited success to date. This has led to increased interest in bioprinting technologies in the field of musculoskeletal tissue engineering. The additive, layer by layer nature of such biofabrication strategies makes it possible to generate zonal distributions of cells, matrix and bioactive cues in 3D. The adoption of biofabrication technology in musculoskeletal tissue engineering may therefore make it possible to produce the next generation of biological implants capable of treating a range of conditions. Here, advances in bioprinting for cartilage and osteochondral tissue engineering are reviewed. Abstract : In this paper, advances in 3D bioprinting for articular cartilage and osteochondral tissue engineering are reviewed. An overview of the field and a description of the current state of the art are provided for the first time. Then, future research directions are discussed and a description of how emerging bioprinting strategies could be used to engineer functional implants for joint regeneration is given.